Elaine Steinbeck in Bangkok - unknown:::Creator::::::::::::
Elaine sitting with an unknown man. This may have been taken at the dinner the Steinbecks had with King Bhumibol Adulyadej (Rama IX) and Queen Sirikit of Thailand. Original in safe